PENGARUH METODE THINK-TALK-WRITE BERBANTUAN GOOGLE DOKUMEN TERHADAP PENINGKATAN KETERAMPILAN MENULIS SISWA SMP - Widianti, Retno Ika Lestari; Sukawati, Sary (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The activity of news writing is part of the productive language skills practice in the Merdeka Curriculum. However, in practice, writing errors in students' news texts still cause information confusion. This study aims to minimize these issues by evaluating the effectiveness of the Think-Talk-Write method aided by Google Docs. The research utilizes a quantitative experimental method, implementing one Group Pre-test and Post-test design. The steps include problem identification, hypothesis formulation, data collection & testing, hypothesis testing, and data interpretation. The intervention population consists of 40 samples from Class 7C of SMP Negeri 5 Cimahi. The students' news text scores and related comprehension were analyzed using descriptive statistics, including score tabulation, the Shapiro-Wilk test, Levene’s test, and the T-Student test. The study revealed that this method of intervention resulted in better student writing. The trial showed an average student writing skill score increase of over 20%, with the highest final score being 95 out of 100. The p-value in the final test was 0.013, with a significance level of 0.05 and CI 95% = (75.197, 76.603). These findings demonstrate that the Think-Talk-Write method aided by Google Docs, as part of the AI ecosystem, significantly improved students' news writing skills. Therefore, this method is adivised for application in the learning process.